2002
DOI: 10.1080/08880010252899370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Children With Immune Thrombocytopenic Purpura Treated With Intravenous Immunoglobulin G or Megadose Methylprednisolone or Observed Without Therapy

Abstract: The authors compared the prognosis in 50 children with acute immune thrombocytopenicpurpura (ITP) who received intravenous immunoglobulin G (IVIG), megadose methylprednisolone (MDMP), or no therapy. Twenty-six children were observed with no therapy, 12 children received IVIG, and 12 children received MDMP. The percentage of the patients whose platelet counts increased at a level of > 20 x 10(9)/L and > 50 x 10(9)/L at 3 days after starting therapy was significantly higher in both IVIG and MDMP groups than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
2
30
0
2
Order By: Relevance
“…Commonly used therapeutic modalities for this disorder include systemic corticosteroids, anti-D IgG, or both or IGIV. 57 This is one of the FDA-approved indications for IGIV, and the ability of IGIV to increase platelet counts in this setting is supported by numerous data. [59][60][61][62] The mechanism of action is believed to be mediated by immunomodulatory capacity exerted by Fc receptor blockade and potentially through ligation of inhibitory Fc receptors.…”
Section: Hematologic Autoimmune Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…Commonly used therapeutic modalities for this disorder include systemic corticosteroids, anti-D IgG, or both or IGIV. 57 This is one of the FDA-approved indications for IGIV, and the ability of IGIV to increase platelet counts in this setting is supported by numerous data. [59][60][61][62] The mechanism of action is believed to be mediated by immunomodulatory capacity exerted by Fc receptor blockade and potentially through ligation of inhibitory Fc receptors.…”
Section: Hematologic Autoimmune Diseasementioning
confidence: 93%
“…Pharmacologic treatment of children with immune thrombocytopenic purpura is an actively debated issue because the vast majority of children recover spontaneously. [56][57][58] Regardless, treatment is usually provided for those children at the greatest risk for complications relating to bleeding or those having chronic refractory disease. Commonly used therapeutic modalities for this disorder include systemic corticosteroids, anti-D IgG, or both or IGIV.…”
Section: Hematologic Autoimmune Diseasementioning
confidence: 99%
“…In our analysis, children with ITP initially treated with IVIG were more likely to have platelet counts ‡150 · 10 9 /l and ‡50 · 10 9 /l at 6 months from diagnosis than children initially receiving no or other drug treatment. Among studies involving randomization between corticosteroids and IVIG and with a follow-up of at least 6 months, none have demonstrated a significant long-term effect in favour of IVIG treatment (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003). However, a recent meta-analysis of these nine studies (Imbach et al, 1985;Blanchette et al, 1993Blanchette et al, , 1994Ozsoylu et al, 1993;Albayrak et al, 1994;Fujisawa et al, 2000;Ancona et al, 2002;Duru et al, 2002;Erduran et al, 2003) found a statistically significant beneficial effect of IVIG 6 months after diagnosis (Beck et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Duru et al enrolled 26 children with a platelet count Ͻ 20 ϫ 10 9 /L and consented them to observation without drug treatment. 21 Ten (38%) had mucosal bleeding at presentation. Only 2 of the 26, both with epistaxis at diagnosis, required further intervention during the follow-up period, which ranged from 5-32 months.…”
Section: Question: Do You Treat This Child With Medication At This Time?mentioning
confidence: 99%